Emergence of a novel calcium signaling pathway in plants: CBL-CIPK signaling network - Pandey, Girdhar K. (Springer-Verlag, 2008)
In the environment, plants are exposed to plethora of adverse stimuli such as abiotic and biotic stresses. Abiotic stresses including dehydration, salinity and low temperature poses a major threat for crop productivity. Plant responds to these stresses by activating a number of signaling pathways which enable them to defend or adjust against these stresses. To understand the mechanisms by which plants perceive environmental signals and transmit these signals to cellular machinery to activate adaptive responses is of fundamental importance to biology. Calcium plays a pivotal role in plant responses to a number of stimuli including pathogens, abiotic stresses, and hormones. However, the molecular mechanisms underlying calcium functions are poorly understood. It is hypothesized that calcium serves as second messenger and, in many cases, requires intracellular protein sensors to transduce the signal further downstream in the pathways. Recently a novel calcium signaling pathway which consist of calcineurin B-like protein (CBL) calcium sensor and CBL-interacting protein kinase (CIPK) network as a newly emerging signaling system mediating a complex array of environmental stimuli. This review focuses on the overview of functional aspects of CBL and CIPK in plants. In addition, an attempt has also been made to categorize the functions of this CBL-CIPK pair in major signaling pathways in plants.